A comparative study of trough profile and operating parameters performance in spiral concentrator. Issue 9 (2nd September 2021) - Ye, Guichuan; Huo, Yayang; Li, Chunfeng; Deng, Chao; Yu, Yuexian; Huang, Gen; Ma, Liqiang
ABSTRACT: Trough profile is an important structural parameter of the spiral concentrator. However, limited attention has been focused on the influence of trough profile on coal separation. In the present work, 21 sets of experiments were carried out to investigate the impact of operating parameters and trough profile on the separation performance. Results show that particles tend to transport outward with the increase of the flow rate and the solid concentration. The cut specific gravity of separation (SG50 ) increases with the flow rate and the solid concentration. The SG50 of the spiral concentrator with the synthetic curve is much lower than that of spiral concentrator with the ellipse or cubic parabola. Light particles prefer to be placed in the outer place of the spiral concentrator with the trough profile of ellipse. Heavy particles tend to report to the inner region of the spiral concentrator with the trough profile of cubic parabola. The spiral concentrator, with the trough profile of cubic parabola in inner place and the ellipse in outer place, is more desirable to separate the coal slime used in this paper. The findings of the present study are of great importance in trough profile optimization of the spiral concentrator.